The Jewish enlightenment - Feiner, Shmuel (Jewish culture and contexts., 2004)
"The Jewish Enlightenment reconstructs the intellectual and social revolution of the Haskalah as it gradually gathered momentum throughout the eighteenth century. Relying on a huge range of previously unexplored sources, Shmuel Feiner fully views the Haskalah as the Jewish version of the European Enlightenment and, as such, a movement that cannot be isolated from broader eighteenth-century European traditions. Critically, he views the Haskalah as truly a European phenomenon and not one simply centered in Germany.